2015
DOI: 10.3390/rel6020476
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Spirituality as a Key Component of Patient Care

Abstract: Patient care frequently focuses on physical aspects of disease management, with variable attention given to spiritual needs. And yet, patients indicate that spiritual suffering adds to distress associated with illness. Spirituality, broadly defined as that which gives meaning and purpose to a person's life and connectedness to the significant or sacred, often becomes a central issue for patients. Growing evidence demonstrates that spirituality is important in patient care. Yet healthcare professionals (HCPs) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 22 publications
3
45
0
3
Order By: Relevance
“…Internationally, most nurses agree that they provide spiritual care as part of their nursing practice [29][30][31] although many are unprepared and may lack supporting education for the assessment or provision of such care [2,31]. The only study conducted in the ROI revealed similar findings [29].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Internationally, most nurses agree that they provide spiritual care as part of their nursing practice [29][30][31] although many are unprepared and may lack supporting education for the assessment or provision of such care [2,31]. The only study conducted in the ROI revealed similar findings [29].…”
Section: Introductionsupporting
confidence: 60%
“…However, even in the presence of recognition of the need for more guidance in the UK, the new NMC Code of Nursing Conduct [23] makes no reference to the spiritual dimension of healthcare [24]. While there is some agreement that spirituality needs to form part of the undergraduate curriculum, approaches vary and significant gaps exist in educational provision [24][25][26][27][28][29]. Internationally, there is a growing belief that professional nurses and midwives need direction regarding spiritual care [30].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that prayer is recognised as a complementary intervention or alternative therapy identified by healthcare professionals as adequate treatment for religious/spiritual disturbances or concerns, because patients considered it significant when it was used [39]. In a holistic paradigm and patient centered care all patients' dimensions should be considered and all needs should be addressed, and this is often included in professional ethical codes and main health policies.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach acknowledges the spiritual distress patients experience and considers spiritual care as one of the components of care provided for the whole person [34]. It demands a spiritual care plan to be part of the treatment plan for every patient.…”
Section: Configuring the Place Of Spirituality In End Of Life Carementioning
confidence: 99%